Transformational Leadership Among Retired Senior Military Officers in the Malaysian Corporate Sector - Stevenson, William R. (1999)
The purpose of this research was to understand the nature of transformational leadership among retired senior military officers as leaders in the Malaysian corporate sector. The research was conducted through the examination of four research questions: (1) what are the characteristics of transformational leaders; (2) what are the specific practices that transformational leaders engage in; (3) what factors are associated with the emergence or practice of transformational leadership; and (4) what aspects of military leadership transfer to the corporate setting. The study employed the qualitative methodology and the data were collected through in-depth interviews, informal observations and examination of related documents. Leaders in the Malaysian corporate sector were purposefully selected to participate in this study. The partici pants included twelve leaders who are retired senior military officers formerly with the Army, Navy and the Air Force and presently holding senior positions in the corporate sector. The interviews were intended to obtain their perceptions, experiences, and practices related to their job as leaders in the corporate sector. The main sources of data were from the semistructured interviews that were taped, transcri bed and analysed. The interviews with the participants were between one to two hours. Apart from the leaders, data was also gathered from five subordinates who were informerly interviewed with the purpose of confirming certain aspects and triangulating the data obtained from the leaders. The study revealed five characteristics of transformational leaders, four aspects of transformational leadership practices, two main factors that influence transformational leadership practices and three main aspects of military leadership that emerged in leadership practices in the corporate environment. Apart from these findings, two other distinct aspects were also discovered to have emerged during the study. These aspects include 'a calling' for leadership prevalent among former military leaders and the need for adjustment from military to the corporate environment.